A escolarização da leitura literária na alfabetização de pessoas adultas e idosas - Daiane Marques Silva (2014)
This study examined conditions in which adult and elderly people read literary texts in elementary school, in the context of Youth and Adult Education. In order to do that, we adopted a social perspective of literacy in the development of this research which is inserted on the discussion field concerning the alphabetization and literacy (SOARES, 2003) and of the literary literacy (COSSON, 2009) for adults and seniors. This is a case study developed through participant observation (BECKER, 1997; TURA, 2003) in a literacy class in a private school during one semester of 2013. Interviews with students and teachers, and observation of sixty-six classes were held. The database developed for this study contains audio and video recordings, field notes and copies of artifacts produced by research participants. Throughout the research process, we sought a rapprochement with the point of view of the participants, with the goal of understanding the meanings of literary reading for the group. Data analysis showed that the place of literature in this education segment is very limited and is subject to the teaching of decoding and working with other curriculum contents. Furthermore, the font size, the texts relevance to the adult world, the access to literary texts in their original support and the chance to talk about the text being read should be considered when facing challenges to adequate schooling of literary reading in the context of basic education for youth, adults and seniors.